Implementasi Bimbingan Kelompok dengan Tekhnik Diskusi untuk Meningkatkan Minat Belajar Peserta - Masya, Hardiyansyah; Efendi, Arifin (Universitas Islam Negeri Raden Intan Lampung, 2015)
The purpose of this study is to increase interest in learning mathematics class XI IPS students SMA Negeri 6 Bandar Lampung using group guidance with discussion techniques. Method used in this study is quasi experimental research. The population of this study is the students of class XI IPSSMA Negeri 6 Bandar Lampung is 119 then the sample of research is 25% ie 30 learners by adjusting the purpose of research using random sampling. The data collection techniques using quesioner, observation, interview and documentation. The result of data analysis The interest of learning in class XII IPS of SMA Negeri 6 Bandar Lampung that there is an increase of learning interest from both experiment and control group. There was 34.77% to 73.44% thus explaining that in the experimental group experienced an increase in learning interest of 38.67% and in the control group from 48.82% to 59.85% this showed that there was an increase in the control group of 11, 03%.